Natural radionuclides contents in marine sediment: evidence for the paleoproductivity - Che Abd. Rahim Mohamed (Universiti Kebangsaan Malaysia, 1997)
A sediment core was obtained at one station in the North Pacific region, and for analyzed uranium, thorium and their daughter nuclides, and combustible fraction. Their concentrations vary considerably in the surface layer but was constant at deeper depth. This variation could be due to the temporal changes on the seabed before being buried in the sediment column. The dilution of aluminosilicate detritus in uranium and thorium nuclides may be occurred. However, the constant concentrations of 230Th at the deeper (30 cm to 110 cm) are due to the past abruption. The calculated sedimentation rate was 1.56 mm/kyr at the surface (0 cm to 30 cm) and 4.55 mm/kyr at the bottom (110 cm to 180 cm) layer.